Unisichtbar, lähmend oder steuernd. Heterogenität als didaktischer Akteur im Unterricht - Reis, Oliver (Heterogenität. Eine Herausforderung für Religionspädagogik und Erziehungswissenschaft)

Modelle als Wege des Theologisierens. Religionsunterricht besser planen und durchführen - Büttner, Gerhard; Reis, Oliver

„Weil man halt ja nebenbei, so etwas gelernt hat…“. Lernortspezifische Jugendtheologie in Schule und Gemeinde

Religion lernen. Jahrbuch für konstruktivistische Religionsdidaktik

„Sie sind doch eine Medienklasse!“. Digitalisierte Praktiken im Religionsunterricht und Implikationen für das professionelle Handeln von Lehrkräften - Reis, Oliver; Caruso, Carina (ÖRF)

Wie meinst du das? Begriffserwerb im Religionsunterricht - Kohlmeyer, Theresa; Reis, Oliver; Viertel, Franziska; Rohlfing, Katharina (Theo-Web)

MigHEFT: DAG-based Scheduling of Migratable Tasks on Heterogeneous Compute Nodes - Lösch, Achim; Platzner, Marco (2020 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW))

LimSt – Ein Fragebogen zur Erhebung von Lernstrategien im mathematikhaltigen Studium - Liebendörfer, Michael; Göller, Robin; Biehler, Rolf; Hochmuth, Reinhard; Kortemeyer, Jörg; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (Journal für Mathematik-Didaktik)

Chancen und Möglichkeiten eines Netzwerks von Mathematischen Lernzentren in Deutschland - Bericht zum digitalen Lernzentrumsworkshop am 22.10.2020 - Schürmann, Mirko; Liebendörfer, Michael; Gildehaus, Lara; Schaper, Niclas; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Kuklinski, Christiane; Ruge, Johanna (dghd-Newsletter)

Ein Kurzbericht aus dem Forschungsprojekt WiGeMath-Lernzentren als Unterstützungsmaßnahme für mathematikbezogenes Lernen in der Studieneingangsphase - Schürmann, Mirko; Schaper, Niclas; Liebendörfer, Michael; Biehler, Rolf; Lankeit, Elisa; Hochmuth, Reinhard; Ruge, Johanna; Kuklinski, Christiane (dghd-Newsletter)

Schadensersatz wegen Verletzung der Bonitätsprüfungspflicht - Bartlitz, David (Zeitschrift für Wirtschaftsrecht (ZIP))

Die Entstehung der Gesellschaft bei eigenmächtigem Geschäftsbeginn - Bartlitz, David (Neue Zeitschrift für Gesellschaftsrecht (NZG))

Der Inverted Classroom in der (digitalen) juristischen Lehre - Bartlitz, David (Zeitschrift für Didaktik der Rechtswissenschaft (ZDRW))

An efficient controlled elitism non-dominated sorting genetic algorithm for multi-objective supplier selection under fuzziness - Hajipour, Vahid; Tavana, Madjid; Santos-Arteaga, Francisco J; Alinezhad, Alireza; Di Caprio, Debora (Journal of Computational Design and Engineering)

An investigation of the robustness in the Travelling Salesman problem routes using special structured matrices - Aziz, Azmin Azliza; Mousavi, Seyed Mohsen; Tavana, Madjid; Niaki, Seyed Taghi Akhavan (International Journal of Systems Science: Operations & Logistics)

INNOVATION DYNAMICS AND FINANCIAL STABILITY: A EUROPEAN UNION PERSPECTIVE - Santos-Arteaga, Francisco Javier; Tavana, Madjid; Torrecillas, Celia; Di Caprio, Debora (Technological and Economic Development of Economy)

Product development team formation: effects of organizational- and product-related factors - Jafari Songhori, Mohsen; Tavana, Madjid; Terano, Takao (Computational and Mathematical Organization Theory)

Supply chain resilience: a benchmarking model for vulnerability and capability assessment in the automotive industry - Kaviani, Mohamad Amin; Tavana, Madjid; Kowsari, Fatemeh; Rezapour, Roghayeh (Benchmarking: An International Journal)

A Review of Uncertain Decision-Making Methods in Energy Management Using Text Mining and Data Analytics - Tavana, Madjid; Shaabani, Akram; Javier Santos-Arteaga, Francisco; Raeesi Vanani, Iman (Energies)

IoT-based enterprise resource planning: Challenges, open issues, applications, architecture, and future research directions - Tavana, Madjid; Hajipour, Vahid; Oveisi, Shahrzad (Internet of Things)

Optimal strategic alliance in multi‐echelon supply chains with open innovation - Tavana, Madjid; Amoozad Mahdiraji, Hannan; Beheshti, Moein; Abbasi Kamardi, Ali‐Asghar (Managerial and Decision Economics)

A practical review and taxonomy of fuzzy expert systems: methods and applications - Tavana, Madjid; Hajipour, Vahid (Benchmarking: An International Journal)

An integrated framework for evaluating the barriers to successful implementation of reverse logistics in the automotive industry - Kaviani, Mohamad Amin; Tavana, Madjid; Kumar, Anil; Michnik, Jerzy; Niknam, Raziyeh; Campos, Elaine Aparecida Regiani de (Journal of Cleaner Production)

A comprehensive framework for analyzing challenges in humanitarian supply chain management: A case study of the Iranian Red Crescent Society - Hashemi Petrudi, Seyed Hamid; Tavana, Madjid; Abdi, Mehdi (International Journal of Disaster Risk Reduction)

A novel optimization model for designing compact, balanced, and contiguous healthcare districts - Farughi, Hiwa; Tavana, Madjid; Mostafayi, Sobhan; Santos Arteaga, Francisco J. (Journal of the Operational Research Society)

A rough based multi-criteria evaluation method for healthcare waste disposal location decisions - Yazdani, Morteza; Tavana, Madjid; Pamučar, Dragan; Chatterjee, Prasenjit (Computers & Industrial Engineering)

A random-fuzzy portfolio selection DEA model using value-at-risk and conditional value-at-risk - Khanjani Shiraz, Rashed; Tavana, Madjid; Fukuyama, Hirofumi (Soft Computing)

A novel method for solving data envelopment analysis problems with weak ordinal data using robust measures - Ebrahimi, Bohlool; Dellnitz, Andreas; Kleine, Andreas; Tavana, Madjid (Expert Systems with Applications)

A novel mixed binary linear DEA model for ranking decision-making units with preference information - Ebrahimi, Bohlool; Tavana, Madjid; Toloo, Mehdi; Charles, Vincent (Computers & Industrial Engineering)

Redundancy allocation problem with multi-state component systems and reliable supplier selection - Zaretalab, Arash; Hajipour, Vahid; Tavana, Madjid (Reliability Engineering & System Safety)

A new model for evaluating subjective online ratings with uncertain intervals - Santos-Arteaga, Francisco J.; Tavana, Madjid; Di Caprio, Debora (Expert Systems with Applications)

A neutrosophic enhanced best–worst method for considering decision-makers’ confidence in the best and worst criteria - Vafadarnikjoo, Amin; Tavana, Madjid; Botelho, Tiago; Chalvatzis, Konstantinos (Annals of Operations Research)

A Malmquist productivity index for network production systems in the energy sector - Tavana, Madjid; Khalili-Damghani, Kaveh; Santos Arteaga, Francisco J.; Hashemi, Arousha (Annals of Operations Research)

A dynamic decision support system for evaluating peer-to-peer rental accommodations in the sharing economy - Tavana, Madjid; Mousavi, Sayed Mohammad Hossein; Mina, Hassan; Salehian, Farhad (International Journal of Hospitality Management)

A novel multi-objective co-evolutionary approach for supply chain gap analysis with consideration of uncertainties - Jafarian, Ahmad; Rabiee, Meysam; Tavana, Madjid (International Journal of Production Economics)

A new dynamic two-stage mathematical programming model under uncertainty for project evaluation and selection - Tavana, Madjid; Khosrojerdi, Ghasem; Mina, Hassan; Rahman, Amirah (Computers & Industrial Engineering)

Zwischen emotionaler Verwundbarkeit und Wissensdrang - Zur Fragen generierenden Wirkung eines literarästhetisch anspruchsvollen zeitgeschichtlichen Bilderbuchs - Kanning, Julian; Kruse, Iris (Das narrative Bilderbuch. Türöffner zu literar-ästhetischer Bildung, Erzähl- und Buchkultur)

Evidence for robust abstract syntactic representations in production before age three - Foltz, Anouschka; Knopf, Karolin; Jonas, Kristina; Jaecks, Petra; Stenneken, Prisca (First Language)
This study investigated whether we can find reliable comprehension-to-production syntactic priming effects in children aged 2;0 to 2;11 and how phonological working memory and sentence production skills relate to the syntactic priming process. A finding of reliable syntactic priming effects would provide strong evidence that children’s syntactic representations are abstracted over individual lexical items. To test children at this young age, they were primed with simple and early-acquired transitive (e.g., tickling (a) baby) and unergative intransitive (e.g., running) syntactic structures. Children aged 2;7 to 2;11, primed with alternating prime structures, revealed a reliable syntactic priming effect. In addition, phonological working memory (moderated by age) and sentence production skills positively affected transitive productions. Children aged 2;0 to 2;6, primed either with alternating or cumulative prime structures, showed no priming effect. Together, the data indicate that children have robust abstract syntactic representations for the tested structures before age three and that both phonological working memory and production skills relate to children’s syntactic priming behavior, albeit in different ways.

Experimental and Theoretical Study on the Role of Monomeric vs Dimeric Rhodium Oxazolidinone Norbornadiene Complexes in Catalytic Asymmetric 1,2- and 1,4-Additions - Kirchhof, Manuel; Gugeler, Katrin; Fischer, Felix Richard; Nowakowski, Michał; Bauer, Alina; Alvarez-Barcia, Sonia; Abitaev, Karina; Schnierle, Marc; Qawasmi, Yaseen; Frey, Wolfgang; Baro, Angelika; Estes, Deven P.; et al. (Organometallics)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Charge Distribution in Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes: A Combined X-ray, XAS, XES, DFT, Mössbauer, and Catalysis Approach - Benedikter, Mathis; Musso, Janis; Kesharwani, Manoj K.; Sterz, K. Leonard; Elser, Iris; Ziegler, Felix; Fischer, Felix; Plietker, Bernd; Frey, Wolfgang; Kästner, Johannes; Winkler, Mario; van Slageren, Joris; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Stereoselective Chromium‐Catalyzed Semi‐Hydrogenation of Alkynes - Gregori, Bernhard J.; Nowakowski, Michał; Schoch, Anke; Pöllath, Simon; Zweck, Josef; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Electronic Structure of the Hieber Anion [Fe(CO)3(NO)]− Revisited by X-ray Emission and Absorption Spectroscopy - Burkhardt, Lukas; Vukadinovic, Yannik; Nowakowski, Michał; Kalinko, Aleksandr; Rudolph, Julian; Carlsson, Per-Anders; Jacob, Christoph R.; Bauer, Matthias (Inorganic Chemistry)

Kulturelle Teilhabe durch innovative Preiskonzepte steigern. Projekt an der Universität Paderborn - Flath, Beate (Politik & Kultur)

Grundlagenwerk zu einer zentralen Thematik. Irmgard Merkt legt ihre "Musikdidaktik für die eine Schule" vor. - Klingmann, Heinrich (Neue Musikzeitung)

Hiob und das Leiden: Vertrauensfrage - Hiob 2,7-13. Bibelarbeit auf dem Weg am Donnerstag, 20. Juni 2019 - Schroeter-Wittke, Harald; Flath, Beate; König, Bernhard; Venus, Viktoria (Deutscher Evangelischer Kirchentag Dortmund 2019. Dokumente)

A General Benchmarking Framework for Text Generation - Moussallem, Diego; Kaur, Paramjot; Ferreira, Thiago; van der Lee, Chris; Shimorina, Anastasia; Conrads, Felix; Röder, Michael; Speck, René; Gardent, Claire; Mille, Simon; Ilinykh, Nikolai; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 3rd International Workshop on Natural Language Generation from the Semantic Web (WebNLG+))
Keywords: gerbil dice speck moussallem param conrads roeder ngonga

Zulässigkeit einer Nichtabnahmegebühr für den Fall des Nichtzustandekommens eines verhandelten Darlehensvertrags. Anmerkung zu OLG Nürnberg, Urt. v. 17.03.2020 - 14 U 189/19 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Die Bonitätsprüfungspflicht bei Personenmehrheiten im Verbraucherdarlehensrecht - Bartlitz, David; Hoffmann, Jochen (Archiv für die civilistische Praxis (AcP))

§§ 109-130b HGB (Innen- und Außenrechtsbeziehungen der OHG) - Bartlitz, David; Hoffmann, Jochen (Handelsgesetzbuch)

Beethoven und seine Zeit - Janus, Richard (Reformation fmit Beethoven feiern. 31. Oktober 2020)